LEAF PIGMENTS IN PEA CROP: RELATIONSHIP BETWEEN SPAD INDEX AND CHLOROPHYLL CONTENT - Wenneck, Gustavo Soares; Villa e Vila, Vinicius; Saath, Reni; Rezende, Roberto; Lopes Pereira , Gustavo; Conti Mondanez, Bruna Mayara (Revista Brasileira de Engenharia de Biossistemas, 2021)
The contents of leaf pigments are directly related to the conditions of plant development, and the determination is carried out by direct and indirect methods. The aim of this work was to relate the values of the SPAD index with the content of leaf pigments in the pea crop. The determination was carried out on plant’s leaves in the reproductive stage, varying the color from yellowish to dark green. The indirect determination was performed with the SPAD 502 equipment and the direct determination by spectrometry using pure acetone as an extractor. Descriptive, correlation and regression analysis were performed on the data. The SPAD index obtained ranged between 8.2 and 42.2. The absolute chlorophyll content is high at higher SPAD values, adjusted by quadratic models. High correlation was obtained between SPAD index and leaf pigments (a, b and total chlorophylls) in pea leaves.